The effect of transformational leadership on intention to quit through perceived organisational support, organisational justice and trust - Engelbrecht, A.; Samuel, O.M. (AOSIS (pty) Ltd, 2019)
Background: The literature has extensively presented evidence to establish that employee turnover is costly and destructive to organisational processes and outcomes. Organisations in South Africa are experiencing a high rate of turnover and it is becoming increasingly difficult to retain employees whose skills are critical to organisational success. This provides a compelling necessity to direct research attention to turnover intention in order to avoid actual turnover. Aim: The purpose of this article was to use partial least squares to test the relationships among selected antecedents of intention to quit. Setting: The study was conducted using employees in organisations that were surveyed in both public and private sectors in the Western Cape, Eastern Cape and Gauteng provinces of South Africa. Methods: The study employed a survey research design using a quantitative research strategy. Data collected from 207 conveniently sampled respondents were used to validate a structural model developed through the review of existing literature. A standardised measurement instrument consisting of all the variables under investigation was used for data collection. Results: The results indicate the following path sequences in predicting employee turnover intention: Transformational leadership through perceived organisational support and transformational leadership through organisational justice impact intention to quit. However, the path sequence from transformational leadership through organisational trust impacting intention to quit was not confirmed. Conclusion: A replication of this study using a longitudinal research design is recommended in order to overcome the methodological limitations of the current study. The conceptual model developed in this study provides relationships that could be used as guidelines to effectively manage the retention of key employees in organizations. © 2019. The Authors. Licensee: AOSIS.
South African Journal of Economic and Management Sciences
Keywords: Employee turnover; Intention to quit; Organisational justice; Organisational trust; Perceived organisational support; Structural equation modelling; Transformational leadership